Capsicum baccatum (Andean Chilli)-assisted phytosynthesis of silver nanoparticles and their H2O2 sensing ability. (18th August 2022) - Kumar, Brajesh; Smita, Kumari; Awasthi, Satish Kumar; Debut, Alexis; Cumbal, Luis
Abstract: In the present study, we report a simple and ecofriendly phytosynthesis of silver nanoparticles (AgNPs) using fruits of Capsicum baccatum L. (Andean chili). During the reaction, the phytoconstituents of C. baccatum act as a reducing and stabilizing agent. Phyotsynthesized AgNPs were characterized through various spectroscopy and microscopic techniques. The produced AgNPs showed a plasmon band at λ max = 458 nm and stable for 10 days, confirmed by UV-vis spectroscopy. Transmission electron microscopy (TEM) explained that the produced AgNPs were quasi-spherical in shape with an average size of 10–30 nm and small aggregation. The X-ray diffraction analysis confirmed the crystalline nature of the AgNPs. Aggregation of AgNPs was indicated in the dynamic light scattering (DLS) and TEM analysis. AgNPs also exhibited quenching/sensing activity of H2 O2 (>50%) at room temperature. The results demonstrate that as-synthesized AgNPs are inexpensive, sustainable and could be an alternative as optical chemical sensors.